Conflict and Cultural Heritage: A Moral Analysis of the Challenges of Heritage Protection - Helen Frowe (Getty Publications, 2019)
In the third issue of the J. Paul Getty Trust Occasional Papers in Cultural Heritage Policy series, authors Helen Frowe and Derek Matravers pivot from the earlier tone of the series in discussing the appropriate response to attacks on cultural heritage with their paper,